2013
DOI: 10.1111/acv.12014
|View full text |Cite
|
Sign up to set email alerts
|

Does colour matter? The influence of animal warning coloration on human emotions and willingness to protect them

Abstract: The perceived popularity of animals plays a crucial role in their support by the general public and consequently in the success of conservation efforts. We experimentally investigated with Slovak schoolchildren the role of animal coloration and basic human emotions in the willingness to protect animals. Both unaltered and experimentally manipulated pictures of aposematic animals increased perceived danger. Spiders and snakes were perceived as more dangerous/disgusting than other taxa, particularly birds and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
94
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(124 citation statements)
references
References 72 publications
(129 reference statements)
12
94
2
2
Order By: Relevance
“…Thus, exposure to animals of fearful or disgusting taxa might be a method to reduce these basic negative emotions which, in turn, may foster the attitude towards their function in ecosystems and conservation. The reduction of disgust is a worthwhile task because disgust negatively impacts on motivation and achievement (Randler et al, 2005;Randler et al, 2013) and the willingness to protect those (Prokop and Fančovičová, 2013). However, the study also showed that photographs reduced disgust.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Thus, exposure to animals of fearful or disgusting taxa might be a method to reduce these basic negative emotions which, in turn, may foster the attitude towards their function in ecosystems and conservation. The reduction of disgust is a worthwhile task because disgust negatively impacts on motivation and achievement (Randler et al, 2005;Randler et al, 2013) and the willingness to protect those (Prokop and Fančovičová, 2013). However, the study also showed that photographs reduced disgust.…”
Section: Discussionmentioning
confidence: 87%
“…Negative emotions, such as anxiety and disgust, are related to lower achievement (Randler et al, 2005) and less willingness to protect disgusting species (Prokop and Fančovičová, 2013), while positive emotions, like interest and well-being are positively related to learning achievement and motivation (Randler et al, 2012b). Disgust reactions are usually hard to unlearn (Kasperbauer, 2015), but studies in clinical settings on phobia (e.g., spider or snake phobia) showed that an intervention with living animals can reduce this phobia, lending support for these types of intervention (Ballouard et al, 2012).…”
mentioning
confidence: 99%
“…It may also depend on the different avifauna in the countries because Colombian species might be more attractive and their song might be more exciting as compared to European avifauna. Prokop and Fančovičová (2013), for example, found that attractiveness positively influences students' willingness to protect the species. It is likely that the link between an interest in birds and their attractiveness worked in this case, too.…”
Section: Discussionmentioning
confidence: 99%
“…For example, birds are most active during the day, and they use acoustic communication, which makes them "more similar" to humans as compared to fish or reptiles. Furthermore, color perception of humans (trichromatic) and birds (tetrachromatic) are more similar than the vision of most other mammals (dichromatic); thus, colors may also seem to play a significant role in attitudes toward birds (Frynta, Lišková, Bültmann, & Burda, 2010;Prokop & Fančovičová, 2013). Concerning human attitudes toward animals, Serpell (1986Serpell ( , 2004 proposed a motivational framework with two distinct dimensions: affection/sympathy and economic self-interest.…”
Section: Attitudes Toward Birdsmentioning
confidence: 99%
See 1 more Smart Citation